Peningkatan Kepedulian Siswa di Rumah Belajar Pelita Kehidupan melalui Penanaman Bunga di Waena Distrik Heram Kota Jayapura - Avelinus Lefaan; Ferry Rhendra Pananda Putra Sitorus; Irene Daniella Merahabia (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
Various floods in Jayapura City in early 2025 have caused a number of losses. The problem of the impact of this flood can be solved by reducing the occurrence of flooding again, especially in the long term through the formation of children's character who care about the environment. Activities to increase environmental awareness were carried out by planting flowers focused on children studying at the Rumbel Pelita located at Kali Sunyi, Polda Bhayangkara Public Housing Complex, Buper Waena. The purpose of this community service activity was to increase children's awareness of the surrounding environment through flower planting. The problem posed was how to change children's behavior to care about the environment to prevent flooding. The solution was to increase children's awareness through flower planting at the Kali Sunyi location, Polda Bhayangkara, Buper Waena, Heram District. The method used was through counseling, question and answer sessions, and flower planting activities accompanied by their care. This care was carried out primarily during the learning process at the Rumbel that took place in the future after the community service activity. The results of this community service have been carried out by planting approximately 165 flowers at the Rumbel location, planted by 50 children.